SOCIODEMOGRAPHIC PROFILE OF INTRAVENOUS DRUG USERS RECEIVING OPIOID SUBSTITUTION THERAPY AT LADY HARDINGE MEDICAL COLLEGE, NEW DELHI (Journal of Forensic Medicine & Toxicology, 2019)
Background: Substance use has become a major threat to our society. Substance use emerged as the topic of concern worldwide because of its health impacts, social and economic consequences. Objective: To assess the socio-demographic profiles of the ‘Injecting drug Users (IDU)’ attending the Opioid Substitution Therapy (OST) at Lady Hardinge Medical College and Associated Hospitals, New Delhi. Methods: Subjects were interviewed personally through oral questionnaire method. Information on socio demographic factors were collected from 100 substance users who received Opioid Substitution therapy during the study period (November’ 2016 - March’ 2018) Results: All the substance users attending Drug deaddiction centre were male.Most (36%) of the subjects were found to bein the age group of 26-35 years. 54% were unmarried. 94% wereresiding in nuclear family. 73% were found to be literate who had attended school up to primary to middle level only. 78% were employed mostly in semiskilled or unskilled jobs. 86% substance users were from poor family background. Conclusion: In this study mostly young male adults having low literacy levels and engaged in unskilled or semiskilled jobs were found to be substance users (Injecting Drug Users).
Keywords: Substance Use; Substance Use Disorder; Opioid Substitution Therapy; Socio-demographic Profile